A blueprint for robust crosslinking of mobile species in biogels with weakly adhesive molecular anchors. Issue 1 (December 2017) - Newby, Jay; Schiller, Jennifer; Wessler, Timothy; Edelstein, Jasmine; Forest, M. Gregory; Lai, Samuel
Abstract Biopolymeric matrices can impede transport of nanoparticulates and pathogens by entropic or direct adhesive interactions, or by harnessing "third-party" molecular anchors to crosslink nanoparticulates to matrix constituents. The trapping potency of anchors is dictated by association rates and affinities to both nanoparticulates and matrix; the popular dogma is that long-lived, high-affinity bonds to both species facilitate optimal trapping. Here we present a contrasting paradigm combining experimental evidence (using IgG antibodies and Matrigel®), a theoretical framework (based on multiple timescale analysis), and computational modeling. Anchors that bind and unbind rapidly from matrix accumulate on nanoparticulates much more quickly than anchors that form high-affinity, long-lived bonds with matrix, leading to markedly greater trapping potency of multiple invading species without saturating matrix trapping capacity. Our results provide a blueprint for engineering molecular anchors with finely tuned affinities to effectively enhance the barrier properties of biogels against diverse nanoparticulate species. Biological polymeric matrices often use molecular anchors, such as antibodies, to trap nanoparticulates. Here, the authors find that anchor-matrix bonds that are weak and short-lived confer superior trapping potency, contrary to the prevailing belief that effective molecular anchors should form strong bonds to both the matrix and the nanoparticulates.